Vocational Education Educator: Case Study Educational and Training Institutions Police Academy - Wulandari, Istri; Raharjo, Tri Joko; Widada, Tri; Arbarini, Mintarsih (Proceedings of International Conference on Science, Education, and Technology, 2024)
Vocational education plays an important role in improving the quality of human resources. To get the quality of professional human resources, the role of practitioners and educators who are competent in their fields is very important. For this reason, various adjustments to the competencies of existing educators are needed according to the conditions and needs of students in meeting employment challenges. The aim of this research is to investigate the competencies possessed by teaching staff at the Police Academy Education and Training Institute, where this educational institution implements vocational education to produce professional Police officer graduates. The case study carried out at the Akpol Education and Training Institute was carried out through a qualitative research method. The research was carried out on the Akpol Cadets Level II, to get an overview of the expected to provide an overview of the factual condition of educators. From the results of the research, a conclusion was drawn that seeing the demands of the times, Akpol must immediately conduct analysis and evaluation as well as improvements in the management of educators so that the graduates who will be produced can immediately adjust to the current situation